2003
DOI: 10.4315/0362-028x-66.4.618
|View full text |Cite
|
Sign up to set email alerts
|

Apple Quality, Storage, and Washing Treatments Affect Patulin Levels in Apple Cider

Abstract: Patulin is a mycotoxin produced primarily by Penicillium expansum, a mold responsible for rot in apples and other fruits. The growth of this fungus and the production of patulin are common in fruit that has been damaged. However, patulin can be detected in visibly sound fruit. The purpose of this project was to determine how apple quality, storage, and washing treatments affect patulin levels in apple cider. Patulin was not detected in cider pressed from fresh tree-picked apples (seven cultivars) but was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 32 publications
2
46
0
1
Order By: Relevance
“…One alternative to room storage is the use of packaging materials such as polyethylene, which through their own atmospheric control, have been shown to reduce patulin production in apples [211]. In the same study mentioned previously [206], patulin was not detected in cider from tree-picked apples stored 4 to 6 weeks at 0 to 2 °C, but was detected at levels between 0.97 and 64 µg/Lin stored, tree-picked, unculled fruit. Cider from apples stored in a controlled atmosphere and culled showed 0 to 15.1 µg/L patulin while unculled apple fruit yielded 59.9 to 120.5 µg/Lpatulin.…”
Section: During Apple Harvest Processing and Storagementioning
confidence: 56%
See 2 more Smart Citations
“…One alternative to room storage is the use of packaging materials such as polyethylene, which through their own atmospheric control, have been shown to reduce patulin production in apples [211]. In the same study mentioned previously [206], patulin was not detected in cider from tree-picked apples stored 4 to 6 weeks at 0 to 2 °C, but was detected at levels between 0.97 and 64 µg/Lin stored, tree-picked, unculled fruit. Cider from apples stored in a controlled atmosphere and culled showed 0 to 15.1 µg/L patulin while unculled apple fruit yielded 59.9 to 120.5 µg/Lpatulin.…”
Section: During Apple Harvest Processing and Storagementioning
confidence: 56%
“…However, this process is expensive and labour intensive. Furthermore, patulin can be detected in visibly sound fruit [206] and can spread from rotten areas of apples into sound areas [220]. Two studies have shown that patulin could diffuse 1 to 2 cm from the rotten core in apples [217,221].…”
Section: During Juice Production: Preparation For Crushing Filteringmentioning
confidence: 99%
See 1 more Smart Citation
“…Others, however, do not support this finding: patulin levels in conventional apple-based products ranged from 5.8 to 56.4 µg/kg with an average of 24.76 µg/kg, while in organic products they ranged from 1.4 to 74.2 µg/kg with an average of 28.34 µg/kg (Ritieni, 2003). Readers should not take any of this information as an indictment of organic produce, because patulin concentrations in apples are very sensitive and responsive (both upwards and downwards) to several harvesting techniques, storage conditions, and other processing practices that are irrelevant to the farming system per se (Sydenham et al, 1997;Jackson et al, 2003).…”
Section: Figurementioning
confidence: 99%
“…Thus, our results confirm previous evidence that the absence of visible symptoms of apple fruit rot does not exclude the risk of patulin contamination. Indeed, Jackson et al [36] reported the same finding and detected patulin from visibly undamaged apples at concentrations reaching 15.1 µg/L of cider when controlled storage conditions were maintained. In this context, the Food and Agriculture Organization of the United Nations (FAO) (2003), considered the storage of apples as a critical control point, having a great influence on the risk of patulin contamination.…”
Section: Discussionmentioning
confidence: 48%